INTERPRETIVE POLICY ANALYSIS (IPA) OF THE TRANSFORMATION IN THE HEALTHCARE MODEL IN BULGARIA (TRAKIA JOURNAL OF SCIENCES, 2025)
The Bismarck model was adopted as the official health care system in Bulgaria, after more than forty years of using the Russian Semashko model. This essay examines the failed reform following Bulgaria’s transition to democracy and the adoption of flawed practices that burden patients with direct and indirect treatment costs. The focus is on the functioning of the Bulgarian health care system and on whether it is possible to transform it from the officially adopted Bismarck model into a de facto American-type system based on direct out-of-pocket payments. By applying interpretive policy analysis and considering all arguments, viewpoints, official data, and interpretations, the paper highlights the errors in the organization and the attempted changes in the healthcare system, along with the reasons for their failure. Dissatisfaction with the unreformed system exists across all facets of health care - from the directors of medical facilities, doctors, and medical staff to patients. Patients pay for almost everything in health care, yet a significant portion of this money never reaches the attending physician. While the state claims that a reform has taken place with only minor flaws, the health care system itself is smoothly and steadily transforming into the American health care system. In a country with a low standard of living, high health care costs, paid by patients, decrease health status, quality and length of life negatively impacting the country’s economy both directly and indirectly. This creates a vicious circle that is analysed here using IPA.